1996
DOI: 10.1073/pnas.93.3.1292
|View full text |Cite
|
Sign up to set email alerts
|

Products of DNA mismatch repair genes mutS and mutL are required for transcription-coupled nucleotide-excision repair of the lactose operon in Escherichia coli.

Abstract: To improve our understanding of the mechanism that couples nucleotide-excision repair to transcription in expressed genes, we have examined the effects of mutations in several different DNA repair genes on the removal of cyclobutane pyrimidine dimers from the individual strands of the induced lactose operon in UV-irradiated Escherichia coli. As expected, we found little repair in either strand of the lactose operon in strains with mutations in established nucleotide excision-repair genes (uvrA, uvrB, uvrC, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(87 citation statements)
references
References 39 publications
6
79
1
1
Order By: Relevance
“…This difference could reflect the participation of the MMR proteins, including MutL, in transcription-coupled repair (49). However, contrary to a recent report (39), we found no bias for any specific mutational event to occur on the transcribed versus the nontranscribed DNA strand (Table S3); such a bias could reflect the activity of transcriptioncoupled repair.…”
Section: Discussioncontrasting
confidence: 56%
“…This difference could reflect the participation of the MMR proteins, including MutL, in transcription-coupled repair (49). However, contrary to a recent report (39), we found no bias for any specific mutational event to occur on the transcribed versus the nontranscribed DNA strand (Table S3); such a bias could reflect the activity of transcriptioncoupled repair.…”
Section: Discussioncontrasting
confidence: 56%
“…4A). Many other proteins, including CSB, XPG, and mismatch repair complexes as well as chromatin-remodeling proteins, may also be involved in transcription-coupled repair of oxidized bases in the cell (39,45,49,50). Transcription-coupled repair and its regulation are obviously complex and probably also involve other unidentified proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, MMR recognizes the mismatches in heteroduplex recombination intermediates, preventing completion of recombination between diverged sequences, thus promoting genetic stability (42)(43)(44). More recently, several groups have shown that MMR is involved in the repair of mismatched 8-oxoguanine, which is one of the major base lesions formed after DNA oxidative attack (45), and may participate in the transcriptioncoupled repair pathway (46,47). Cells with a defective MMR show a mutation rate 100-fold greater than that of normal cells, causing the accumulation of potentially deleterious mutations throughout the genome.…”
Section: Discussionmentioning
confidence: 99%